Ray-tracing based Inference Attacks on Physical Layer Security - Walther, Paul; Richter, Markus; Strufe, Thorsten (Electronic Communications of the EASST, 2021)
In wireless network security, physical layer security provides a viable alternative to classical cryptography, which deliver high security guarantees with minimal energy expenditure. Nevertheless, these cryptograhpic primitives are based on assumptions about physical conditions which in practice may not be fulfilled. In this work we present a ray-tracing based attack, which challenges the basic assumption of uncorrelated channel properties for eavesdroppers. We realize this attack and evaluate it with real world measurement, and thereby show that such attacks can predict channel properties better than previous attacks and are also more generally applicable.